A CO2-Driven Gas Lift Mechanism in Geyser Cycling (Uzon Caldera, Kamchatka) - Alexey V. Kiryukhin; Gennady Karpov (Geosciences, 2020)
Here, we report on a new geyser (named Shaman) formed in the Uzon caldera (Kronotsky Federal Nature Biosphere Reserve, Russia) in autumn 2008 from a cycling hot Na-Cl spring. The geyser is a pool-type CO2-gas lift driven. From 2012 to 2018, the geyser has shown a rather stable interval between eruptions (IBE) from 129 to 144 min with a fountain height up to 4 m, and the geyser conduit has gradually enlarged. In 2019, the Shaman geyser eruption mode significantly changed: cold water inflow from the adjacent stream was re-directed into the geyser conduit and the average IBE decreased to 80 min. We observed two eruptive modes: a cycling hot spring (June 2019) and a cycling geyser (after June 2019). Bottom-hole temperature recording was performed in the geyser conduit to understand its activity. The TOUGH2-EOS2 model was used to reproduce the obtained temperature records and estimate geyser recharge/discharge parameters in both modes. Modeling shows that a larger cold inflow into the conduit causes a switch from cycling geyser to hot cycling spring mode. It was also found that the switch to cycling geyser mode corresponds to a larger mass of CO2 release during the time of the eruption.